Rancang Bangun Sistem Kontrol Suhu Berbasis Internet Of Things (IoT) untuk Efisiensi Energi Pendingin Ruangan Menggunakan Metode Prototype - Fiqar Haytsam Muhammad Dzul Qornain; Budi Tjahjono; Gerry Firmansyah; Muhamad Hadi Arfian (CV. Green Publisher Indonesia, 2026)
This research presents a low-cost automatic Air Conditioner (AC) control system designed to improve energy efficiency and thermal comfort. The system utilizes an ESP 8266 microcontroller, a DHT22 sensor to monitor temperature, and a Passive Infrared (PIR) sensor to detect human presence. It is integrated with the Blynk app for real-time monitoring of temperature and AC status. The system operates based on a control logic that activates the AC only when the room is hot and occupied, adjusting its intensity depending on activity levels. The research follows the prototyping model, using the IRac.h library for managing AC communication protocols. Functional testing in six different scenarios confirms that the system operates effectively, turning the AC on only when needed and shutting it off when the room is empty or the target temperature is reached. The proposed prototype successfully automates conventional AC systems, improving both energy efficiency and user comfort.